PENGARUH PEMBERIAN BERBAGAI TINGKAT MIKORIZA ARBUSKULA PADA TANAH ULTISOL TERHADAP PRODUKTIVITAS TANAMAN LEGUMINOSA - andrian mustapa (Universitas Sumatera Utara, 2014)
ABSTRACT Soil ultisol given arbuscular mycorrhizal fungi increased the nutrient content of the soil thereby increased the productivity of legume. The objective of this research to determine the response of various levels of arbuscular mycorrhizal fungi in the soil ultisol on productivity of legume (Arachis glabrata, Centrosema pubescens and Pueraria javanica) as measured by the production of fresh, dry matter production and root biomass. The research conducted at field trial Animal Husbandry Department, Faculty of Agriculture, North Sumatera University at November 2012 until January 2012. The research used three types of legumes L1 (Arachis glabrata); L2 (Centrosema pubescens) dan L3 (Pueraria javanica). The design of this experiment used Completely Randomized Design with 4 treatments. The treatments consist of T0 (0 gram FMA (kontrol)); T1 (5 gram FMA/polybag); T2 (10 gram FMA/polybag) dan T3 (15 gram FMA/polybag). The result of this research showed that granting different levels of arbuscular mycorrhizal on soil ultisol increased the production of fresh (P<0,01),increases dry matter production (P<0,01) and increased root biomass (P<0,05). The conclution of this research is provision of arbuscular mycorrhizal in the planting medium soil ultisol can increased the production of fresh, dry matter production and root biomass of legume crop (Arachis glabrata, Centrosema pubescens dan Pueraria javanica). Keywords: soil ultisol, fungi, arbuscular mycorrhizal, legume